DIVORCE GRANTED BY THE JUDGE OF THE PETALING JAYA SHARIA COURT, SELANGOR, MALAYSIA (ANALYSIS BASED ON THE OPINION OF IMAM SYAFI'I) - Nur Fatin Nadzirah Bt. Ahmad Fuad (Universitas Islam Negeri Sumatera Utara Medan, 2025)
This thesis is titled “ Divorce was done by the Hakam in a Petaling Jaya Selangor Syariah Court, Malaysia” ( Analysis based on the opinion of the Imam Syafi'i). The main problem in this study is, first is to knowing the execution by the Hakam. Second, factors that cause justice can divorce. Third, studied the Imam Syafi'i view of the divorce in lower syariah court of Petaling Jaya Selangor. Researchers use empirical legal examining divorce-related arrangements that is conducted by hakam contained in section 48, Enactmen Islamic Family Law ( Selangor State) 2003. This research uses data collection techniques with library and field studies. The results showed that and several authorized employess. The results showed that the inauguration of hakam was made after the court agreed to the dispute ( shiqaq) that is always in effect in the period of marriage after the completion of peace affairs at the level of the Office of Peace ( Juru Damai) failed or did not find a way out. Therefore, hakam has the role of gaining authority in pronouncing divore rather than husband if the process of reconciliation fails and the husband is reluctant to recite the divorce. The factors which cause hakam to divorce are the first is, royal taqnin as stipulated by the statutory obligation for the people to obey it. Second, defending the fate of women hung without strings. Third, be a solution for the wife if the husband is reluctant to divorce even though it has caused harm. However, in the opinion of the Imam Syafi'i here that does not require a wife to sue for divorce on the grounds of shiqaq. On the contrary, the judge who hears these demands should appoint hakam for the husband and hakam for the wife in order to reconcile the husband and wife. Hakam meant here is not authorised to drop divorce and is only authorised as a representative to reconcile husband and wife.